Stochasticity Versus Determinacy in Neurobiology: From Ion Channels to the Question of the “Free Will” - Braun, Hans Albert (Frontiers in Systems Neuroscience, 2021)
If one accepts that decisions are made by the brain and that neuronal mechanisms are obeying deterministic physical laws it is hard to deny what some brain researchers postulate, e.g. „We do not what we want but we want what we do“ or “„We should stop talking about freedom. Our actions are determined by physical laws”. This point of view has been substantially supported by spectacular neurophysiological experiments demonstrating action related brain activity (readiness potentials, BOLD signals) occurring up to several seconds before an individual becomes aware about his/her decision to perform the action. Such findings will be confronted with other experimental data, supplemented by computer simulations, to demonstrate that biological systems, specifically brain functions, are built up on principle randomness which is already introduced at the lowest level of neuronal information processing, the opening and closing of ion channels. These transitions, indeed, are following physiological laws but apparently also need to make use of randomness – principally unavoidable under all life compatible conditions. This randomness will not necessarily smear out towards higher functional levels but can even amplified by cooperative effects with the system’s nonlinearities. Examples shall be given to illustrate how stochasticity can propagate from ion channels to single neuron action potentials to neuronal network dynamics to the interactions between different brain nuclei up to the control of autonomic functions and consciousness.